1991
DOI: 10.1172/jci115351
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury. Pathogenesis of intraalveolar fibrosis.

Abstract: In patients dying with acute lung injury, interstitial mesenchymal cells migrate into the airspace where they replicate and deposit connective tissue. We therefore hypothesized that peptides capable of promoting mesenchymal cell migration and replication would be present in the alveolar airspace. To examine this hypothesis, patients with severe acute diffuse lung injury (n = 26) underwent bronchoalveolar lavage. Acutely ill patients without lung injury served as controls (n = 12). Recovered effluent was examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 46 publications
2
45
0
Order By: Relevance
“…Strong evidence points away from TNF-␣ as a major modulator of fibroblast phenotype in early ALI, despite its abundance. In contrast, prior work provides convincing evidence for an alveolar mitogenic predominance and a fibroblast mitogenic role for PDGF B chain-related molecules in early (within 3 days) ALI bronchoalveolar lavage fluid (21,55). IL-1␤ can also up-regulate PDGF A chain and PDGFR-␣ in fibroblasts, thereby potentially sensitizing fibroblasts to the mitogenic effects of PDGF (56,57).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Strong evidence points away from TNF-␣ as a major modulator of fibroblast phenotype in early ALI, despite its abundance. In contrast, prior work provides convincing evidence for an alveolar mitogenic predominance and a fibroblast mitogenic role for PDGF B chain-related molecules in early (within 3 days) ALI bronchoalveolar lavage fluid (21,55). IL-1␤ can also up-regulate PDGF A chain and PDGFR-␣ in fibroblasts, thereby potentially sensitizing fibroblasts to the mitogenic effects of PDGF (56,57).…”
Section: Discussionmentioning
confidence: 93%
“…In human acute lung injury, PDGF-related molecules (B chain isoforms) have been identified as one group of mitogens for fibroblasts in the alveolar compartment (21). However, prior work was largely accomplished using samples (bronchoalveolar lavage) that are 100-fold diluted relative to alveolar lining fluid in vivo and that were collected several days after the onset of clinical acute lung injury.…”
mentioning
confidence: 99%
“…PDGF and TGF-␣ are both elevated in alveolar macrophages or bronchoalveolar lavage fluid from patients with pulmonary fibrosis. 8,9,11,28 In rat models of fibrosis, PDGF and the PDGF ␣-receptor subtype are increased 2 to 3 days after lung injury by bleomycin or metals. 4,29 EGF and TGF-␣ are elevated 2 to 4 days in the rat bleomycin model.…”
Section: Discussionmentioning
confidence: 99%
“…FABISIAK et al [61] examined expression of PDGF-B mRNA in the rat lung during chronic hyperoxia, and showed that increased expression of this gene was temporally self-limited. Furthermore, the role of PDGF in patients with adult respiratory distress syndrome (ARDS) is inconclusive [62]. Thus, whilst PDGF probably plays a reparative role after injury, its involvement in the development of fibrosis is much less certain.…”
Section: Growth Factorsmentioning
confidence: 99%